A field system to deliver desired O-3 concentrations in leaf-level gas exchange measurements: Results for Holm oak near a CO2 spring - Grulke, N. E.; Paoletti, E. (PHYTON-ANNALES REI BOTANICAE, 2005)
Conventional gas exchange systems adsorb ozone (O-3) despite attempts to saturate the system prior to measurements. A steady-state, open photosynthetic system was designed and used in the field to supply a small leaf cuvette with conditioned air stream (growth CO2 concentrations, humidified, cooled) and augmented with either background or elevated O-3. Two innovations led to success: 1) supplying the cuvette with cooled air instead of Peltier cooling within the cuvette; and 2) using a custom-designed, low flow (capable of 100 seem), fast response (20 S) O-3 monitor. We tested whether elevated CO2 would alter stomatal response to short term, steady state elevated O-3. Holm oak (Quercus ilex L., Fagaceae), an evergreen broadleaf tree growing near a geothermal CO2 vent, has been exposed over its lifetime to a gradient of CO2 concentrations. We chose trees in areas averaging 450 mu l 1(-1) (low background CO2) and 1500 mu l 1(-1) (super-elevated CO2). Background O-3 exposure at this site is moderate (10 am to 5 pm averages of 62 nl 1(-1) in June). We measured gas exchange at the growth CO2 levels, and at ambient O-3 or 1.7x ambient O-3 concentrations. At low background CO2, short term elevated O-3 depressed foliar transpiration. Because there was little concurrent change in net assimilation, instantaneous transpiration efficiency was increased. At super-elevated CO2, short term elevated O-3 did not affect foliar transpiration. Because there was a concurrent decrease in net assimilation, instantaneous transpiration efficiency was decreased at elevated CO2 and O-3.
The following values have no corresponding Zotero field: pub-location: WIENER STRASSE 21-23, A-3580 HORN, AUSTRIA publisher: FERDINAND BERGER SOEHNE
Keywords: Carbon dioxide; instantaneous transpiration efficiency; ozone exposure; Quercus ilex